2013
DOI: 10.1016/j.tox.2013.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to DEHP decreased four fatty acid levels in plasma of prepartum mice

Abstract: Maternal exposure to di(2-ethylhexyl) phthalate (DEHP) decreased the plasma triglyceride in prepartum mice. To identify the fatty acid (FA) species involved and to understand the underlying mechanisms, pregnant Sv/129 wild-type (mPPARα), peroxisome proliferator-activated receptor α-null (Pparα-null) and humanized PPARα (hPPARα) mice were treated with diets containing 0%, 0.01%, 0.05% or 0.1% DEHP. Dams were dissected on gestational day 18 together with fetuses, and on postnatal day 2 together with newborns. n-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 35 publications
(51 reference statements)
5
29
0
Order By: Relevance
“…Three decades ago, Bell observed that dietary administration of DEHP inhibited cholesterolgenesis and decreased blood lipid levels in multiple animal species (7). More recent rodent models (8, 36) suggest that the hypolipidemic effect of DEHP may arise through its interactions with peroxisome proliferator-activated receptor-α (PPAR-α), a ligand-activated transcription factor that can decrease production of LDL-C and triglycerides, and upregulate HDL-C levels through its roles in lipid oxidation and fatty acid synthesis (37, 38). Likewise, our finding that higher peripubertal MEP was associated with lower total cholesterol and LDL-C could be explained by the fact that MEP is an estrogenic compound that may act as a PPAR-γ agonist (39) to reduce circulating lipid levels by promoting uptake and storage of free fatty acids in adipose tissue (40).…”
Section: Discussionmentioning
confidence: 99%
“…Three decades ago, Bell observed that dietary administration of DEHP inhibited cholesterolgenesis and decreased blood lipid levels in multiple animal species (7). More recent rodent models (8, 36) suggest that the hypolipidemic effect of DEHP may arise through its interactions with peroxisome proliferator-activated receptor-α (PPAR-α), a ligand-activated transcription factor that can decrease production of LDL-C and triglycerides, and upregulate HDL-C levels through its roles in lipid oxidation and fatty acid synthesis (37, 38). Likewise, our finding that higher peripubertal MEP was associated with lower total cholesterol and LDL-C could be explained by the fact that MEP is an estrogenic compound that may act as a PPAR-γ agonist (39) to reduce circulating lipid levels by promoting uptake and storage of free fatty acids in adipose tissue (40).…”
Section: Discussionmentioning
confidence: 99%
“…FA levels in maternal blood were determined duplicately by GC-MS as described in detail in our earlier study [17] after extracting lipids according to the method of Folch et al [22]. Nine FA species targeted for measurement included palmitic and stearic acids of saturated FAs, palmitoleic and oleic acids of monounsaturated FAs, LA and arachidonic acid (AA) of the n-6 family, and ALA, eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) of the n-3 family.…”
Section: Fa Profiles In Maternal Bloodmentioning
confidence: 99%
“…Moreover, prenatal DEHP exposure was reported to correlate with shorter anogenital distance, reduced penile size and incomplete testicular descent [13,14], more non-optimal reflexes [15] and reduced masculine play behavior [16] in male infants, suggesting that possible sex difference exists in DEHP toxicity. Additionally, our group recently reported that maternal exposure to DEHP decreased plasma levels of triglycerides (TG) [1] and four fatty acid (FA) components [17] in prepartum mice, including palmitic acid, oleic acid, linoleic acid (LA), and a-linolenic acid (ALA), which was suspected to correlate with adverse effects of DEHP. However, no information regarding humans is available.…”
Section: Introductionmentioning
confidence: 99%
“…Human exposure to DEHP is reported to be mainly through ingestion and dermal contact [3]. In recent years, a number of studies have shown that exposure to DEHP can cause abnormal lipid metabolism in humans, which results in numerous health implications such as heart disease, diabetes, and as the most common disorder, obesity [4,5,6]. …”
Section: Introductionmentioning
confidence: 99%